If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + 9d = 12d Solving 18 + 9d = 12d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-12d' to each side of the equation. 18 + 9d + -12d = 12d + -12d Combine like terms: 9d + -12d = -3d 18 + -3d = 12d + -12d Combine like terms: 12d + -12d = 0 18 + -3d = 0 Add '-18' to each side of the equation. 18 + -18 + -3d = 0 + -18 Combine like terms: 18 + -18 = 0 0 + -3d = 0 + -18 -3d = 0 + -18 Combine like terms: 0 + -18 = -18 -3d = -18 Divide each side by '-3'. d = 6 Simplifying d = 6
| 10t+17=-17+12t | | 4x^2-y^2=256 | | 5-x-2y=0 | | -(6y+4)-(5y-7)=1 | | 3b^3+9b=0 | | 121-6x=12x+23 | | 5x+3=7x+-3 | | -6(6y+4)-(-5y-7)=1 | | 3(n+6)=-9 | | 4(7x-1)=3(2x-1)-4(x+6) | | (-2/5)3 | | w^2+16w+64=0 | | 5x+6=106 | | X^2=80X | | 4-3p=-2 | | 10v=60 | | 2(3-w)+6=-6(w-2)-7 | | 0(-8/7) | | X^2=34X | | -6/7w=-42 | | 4x^2-24x=-27 | | -8/15-23/25 | | 1/3(3x-9)=-10+6+3(2-x) | | 6(2x+1)=10x+4 | | 12x-10=10x-6 | | 0=4(-4x^2+10x-6) | | 3(x+14)=69 | | z^2+6z-27=0 | | -36=4v+4(v+7) | | 5/6*2/3=x | | -19/35+4/15 | | 3x^2+5=65 |